Improving Student Learning Outcomes through the Use of Website-Based Learning Media in Elementary Schools - Setyana Laspar Vianti; Nur Faidah; Fathia Filma Nukiki (Universitas PGRI Semarang, 2026)
This study aims to improve students' learning abilities by using website-based learning media for metamorphosis material for fourth-grade students at Cempereng State Elementary School. This study was motivated by low student learning outcomes due to the lack of use of visual and interactive media in science learning. This study is a Classroom Action Research (CAR) that took place in two cycles. The subjects were 23 fourth-grade students. Data were collected through learning outcome tests, observations, and questionnaires. The results showed that the average student score increased from 66.3 in the pre-action stage to 74.1 in the first cycle and 83.2 in the second cycle. The learning completion rate also increased from 39.1% to 91.3%. Website-based learning media is able to present material in an interesting way by using a combination of text, images, videos, and interactive quizzes. In addition, student participation and enthusiasm for learning also increased. Thus, website-based learning media has proven effective in improving student learning outcomes and can be used as an alternative science learning that suits the needs and characteristics of elementary school students